PERENCANAAN PERLUASAN APRON DI BANDAR UDARA KALIMARAU - Ferdhyo Nanda Pratama; Safitri Nur Wulandari; Wiwid Suryono (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Kalimarau Berau Airport is an airport managed by UPBU (Airport Operator Unit) under the auspices of the Directorate General of Civil Aviation. Kalimarau Airport plays an important role in economic growth and is a tourist gateway for the surrounding area. During the last 10 years the number of passengers from 2010 to 2019. This study aims to fulfill the apron capacity at Kalimarau Berau Airport for the next 10 years by using linear regression forecasting methods, and planning the thickness of the pavement structure with an annual departure in 2029 that has been obtained, and get the PCN value from the thickness of the design pavement structure. The results of this study are the apron capacity in the planning year until 2029, the planned aircraft movements are 5401 aircraft movements. With a monthly movement of 459 aircraft movements, 20 aircraft movements on busy days, 11 movements during peak hours, and 12 parking stands planned to be 485.6 m wide and 100 m wide. For the results of the pavement structure using manual FAA consisting of 38 cm thick concrete slab, 13 cm thick stabilized base ,thick base 24 cm with subgrade 6% CBR. Based on the RAB calculation, the budget needed to carry out construction work rigid for the expansion of the apron with an area of ​​19,760 m2 is Rp. 58.583.748.460,00.